2020
DOI: 10.1088/1361-665x/ab8fcc
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic energy harvesting enhanced by locally resonant metamaterials

Abstract: Acoustic energy harvesting has the potential to power small-scale electronic applications and attracts wide attention. This paper presents a two-dimensional local resonant metamaterial energy harvester. The defect in the metamaterial which can induce local resonance is utilized to enhance energy harvesting. The defect mode and key parameters of the local resonant metamaterial energy harvester which can generate the maximum voltage are determined by theoretical analysis and simulations. The experiments were con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…Also, a recent experiment by Ma et al 61 on metamaterial, in which the energy harvesting has been demonstrated at the defective site in metamaterial, that site could induce the local resonance. This experiment was conducted in hermi-anechoic room and here the maximum generated output voltages are determined by simulations and theoretical analysis.…”
Section: Acoustic Metamaterial-based Approachesmentioning
confidence: 98%
See 1 more Smart Citation
“…Also, a recent experiment by Ma et al 61 on metamaterial, in which the energy harvesting has been demonstrated at the defective site in metamaterial, that site could induce the local resonance. This experiment was conducted in hermi-anechoic room and here the maximum generated output voltages are determined by simulations and theoretical analysis.…”
Section: Acoustic Metamaterial-based Approachesmentioning
confidence: 98%
“…Figure 21. The simulation of the concentration of energy density at the defective site of metamaterial 61. …”
mentioning
confidence: 99%
“…The case for using metamaterials to enhance energy harvesting lies in their unique properties to slow down the propagation of elastic waves and focus the mechanical energy within or close to a bandgap. Therefore, the high-capability target of PEH can be naturally addressed using metamaterials [25]. Since the harvested power is noticeable only close to the bandgap frequency [19], hence in rather narrow band, graded resonant designs [26] could be ideal to tackle the broadband target.…”
Section: Introductionmentioning
confidence: 99%
“…Enhancing acoustic transmission between two different media has broad applications in acoustic imaging, energy conversion, , acoustic detection, and sensing, etc. Due to the acoustic impedance mismatch, only a little acoustic energy can transmit across different media, especially across the interface of different phases such as solid, water, and air .…”
Section: Introductionmentioning
confidence: 99%
“…Second, the transmission at intermediate frequencies remains a challenge. Currently, most resonant units of metamaterials are smaller than the operating wavelength by 2 orders of magnitude, hence they usually work at frequencies lower than 10 kHz where the resonators are mm-scale and above. ,,,, The operation of intermediate frequencies such as 10–100 kHz is difficult for practical applications, because they correspond to microscale resonators that require sophisticated fabrication techniques. Since underwater ultrasonic sensors , usually work at 10–50 kHz, the intermediate-frequency acoustic transmission will have significant sonar applications. Lastly, wide-angle acoustic transmission across the water–air interface has not yet been achieved …”
Section: Introductionmentioning
confidence: 99%